31.2 Nordsamisk i Norge: Sammendrag av ELDIA-delstudierapport - Marjomaa, Marko
Report on the case study on the North Sámi language in Norway, conducted within the EU-FP7 research project ELDIA. Abridged version translated into Norwegian.